RISK MANAGEMENT OF TIE BACK REDESIGN ON THE CENGKARENG DRAIN - Egy Nafriro Lazuardi; Endah Kurniyaningrum (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The coastal area of ​​North Jakarta faces significant pressure due to land subsidence, sea level rise, and complex hydrodynamics. These conditions increase the risk of failure of coastal protection structures, especially in retaining walls with corrugated concrete sheet piles (CCSP). This study aims to analyze risk management in the redesign of the coastal protection tie-back system at the Cengkareng Drain site, DKI Jakarta. The research method combines qualitative and quantitative approaches through field observations, document studies, expert interviews, and risk analysis using Failure Mode and Effect Analysis (FMEA) and Analytic Hierarchy Process (AHP). The analysis results indicate that technical risks in the form of slope instability and lateral deformation of the CCSP are prioritized risks with a very high category. The application of the tie-back system in the redesign was able to reduce lateral deformation from 59.6 cm to 37.1 cm and increase the safety factor to 1.521. This study confirms that an integrated risk management approach is effective in supporting decision-making for more reliable and sustainable coastal protection structure redesign.